Cross-docking based factory logistics unitisation process: An approximate dynamic programming approach - Lyu, Zhongyuan; Huang, George Q. (European journal of operational research, 2023)
•Novel integer program model for the combination of truck docking scheduling and line feeding process is formulated.•Solution approaches based on approximate dynamic programming (ADP) framework are developed.•The proposed time-varying value function approximations capture the status characteristics over time, reduce the approximation parameters and speed up convergence significantly.•The proposed ADP can generate high-quality solutions far more efficiently than the commercial solver. The factory logistics increases in importance as more processes and types of components are needed to produce a product. Due to the limited industrial space and stressful competitive environment, manufacturers increasingly outsource logistics-related activities to Third-Party Logistics (3PLs) and Supply hubs. However, the challenges, including unsynchronised decisions with other partners, non-value-added warehousing operations, and excessive space occupation, still burden manufacturers. This research proposes a cross-docking-based factory logistics unitisation process (CD-FLUP) that integrates the cross-docking technique into the assembly line feeding process and uses mobile shelves for component holding and delivery. We formulate the CD-FLUP with an integer program to minimise the total number of shelf units put into storage and the number of deliveries to assembly lines. Based on time decomposition, we propose an approximate dynamic programming (ADP) approach to solve the model efficiently. The time-varying value function approximation (VFA) developed in the proposed ADP approach reduces the approximation parameters and speeds up convergence significantly. The numerical experiment shows that the proposed ADP can generate high-quality solutions far more efficiently than a commercial solver.